ANALYSIS OF INTERNAL CONTROL OVER FINANCIAL REPORTING (PIPK) IN THE INSPECTORATE OF CENTRAL PAPUA PROVINCE - Muslimin, Muslimin; Baharuddin, Baharuddin; Malissa, Mika (Journal of Entrepreneur, Business and Management, 2025)
This study analyzes the effectiveness of Internal Control over Financial Reporting (PIPK) in the Inspectorate of Central Papua Province. Using a qualitative approach, this study collected data through observation, interviews with 15 Inspectorate employees, and documentation. The results of the study indicate that employee capacity in implementing PIPK is influenced by system understanding, training needs, work experience, and certification in accounting and finance. The main inhibiting factors in internal control include lack of training, high employee turnover, lack of awareness of the importance of internal control, and technological limitations. To improve the accuracy and transparency of financial reporting, the Inspectorate implements various strategies, such as attending training and workshops, conducting periodic reviews, using accounting software, and involving third parties in independent audits. This study recommends increasing employee capacity through continuous training and optimizing the use of technology to strengthen the internal control system in the public sector.